Application of art education in the management and reduction of signs of fatigue in women with MS diagnosis - Egidijus Elijošius; Adolfas Juodraitis; Andrius Kazlauskas; Virginija Nemeikšienė; Liuda Radzevičienė; Rimantas Pranckaitis (Social Welfare: Interdisciplinary Approach)
In the article presented results reveal dimensions of infl uence of art education on the reduction of fatigue in patients with MS. Personal motivation for active participant in social life could be promoted by optimizing common art education activities that have signifi cant impact on reduction of fatigue signs. All too often, problems of fatigue in MS fi rst of all are similar to somatic and neurological problems, but from the point of view of social paradigm – person’s fatigue problems deal with effective social participation and social involvement. Fatigue as a certain person’s inwardly status is closely connected with emotional self-feeling and hopefully could be managed applying art education. Subjective understanding of signs of fatigue and its management reveals ways of specifi c educational activities of adults with MS that are directly pointed to the reducing sense of fatigue and increasing quality of social participation.